Respon Pertumbuhan Bibit Anggrek Dendrobium sp. pada Saat Aklimatisasi terhadap Beragam Frekuensi Pemberian Pupuk Daun - RINDANG DWIYANI (Fakultas Pertanian Universitas Udayana, 2012)
The aim of the experiment was to investigate the appropriate frequency of foliar fertilizer applicationof Hyponex and Gandasil D for the growth of seedlings of Dendrobium sp. at acclimatization stage.Various frequency of application for both foliar fertilizers were trialed, i.e. once in 5 days, once in 10days, once in 15 days and control (without fertilizer). The results showed that the most appropriatefrequency for the application of Hyponex and Gandasil D for seedlings of Dendrobium sp. was once inevery 10 days.